ANALISIS YURIDIS TERHADAP PELAKU ABORSI DITINJAU DARI UNDANG-UNDANG NOMOR 36 TAHUN 2009 TENTANG KESEHATAN - Kurniahati Hulu (Jurnal Panah Hukum, 2023)
Abortion is a form of crime against the lives of unborn babies. This is done because there are two things, namely the desire of the woman who is pregnant because of a problem which is an indication of a medis emergency or because it is the wish of a certain party due to the disgrace of an unwanted pregnancy. In this study, the authors summarize one formulation of the problem, namely how the juridical analysis of abortion actors is viewed from Law Number 36 of 2009 concerning Health. This study aims to find out and understand how the position of criminal law is regarding the crime of abortion when viewed from Law Number 36 of 2009 concerning Health. The type of research conducted is normative legal research with data collection techniques using secondary data consisting of primary, secondary and tertiary legal materials. Data analysis used in this study used qualitative data analysis to produce descriptive data. Based on the research findings and discussion, it can be concluded that the act of abortion is a prohibition in health practice. However, in certain circumstances the act of abortion can be legalized in accordance with the provisions in Article 75 paragraph (2) of Law Number 36 of 2009 concerning Health. The act of abortion can be said to be a crime if in that person there is an element of intention to have an abortion. Someone who intentionally has an abortion other than a medical emergency and a victim of rape can be subject to criminal sanctions as stipulated in Article 194 of the Health Law. As for the author's suggestion, namely that women should take better care of themselves to avoid early pregnancies or get pregnant out of wedlock, so that it does not lead to thoughts of having an abortion and the public knows about legal sanctions when someone commits an illegal abortion